A sustainable future for small-scale farming?: qualitative research on agroecology and digitalization - Binetsch, Jonathan; Bun, Hikari; Westpfahl, Rafael Hernández; Krug, Jana; Lehmann, Rosa; Bravo, Eva Sulca; Walter, Caroline; Weise, Teresa (HCIAS working papers on Ibero-America, 2023)
There is a great deal of agreement amongst farmers, environmentalists, scholars, and policy-makers that the current agri-food-system is unsustainable. Debates about the future of an agriculture that can cope with the challenges of climate change and at the same time feed many people well revolve, among other things, around a digitalization of agriculture, but also around alternative agricultural practices and sciences. Agroecology represents one such alternative. However, in view of the processes toward digitized agriculture, the question arises as to whether digitization and agroecology are compatible.This working paper approaches this question from the perspective of environmental and development NGO activists as well as academics researching these topics. Based on qualitative interviews, the paper shows the multiple challenges and partly diverging perspectives on (possible) costs and benefits of digitization for agroecological practices and those who practice them.